Livable cities? : urban struggles for livelihood and sustainability - Evans, Peter B., 1944- (University of California Press, 2002)
The cities of the developing world are hubs of economic growth but they are increasingly ecologically unsustainable and unliveable. This book explores the issues of livelihood and ecological sustainability in cities of the developing world.